The Gild of Zeus Hypsistos - Roberts, Colin (Harvard theological review, 1936)
The text is written on a single sheet of papyrus cut from a roll; a join runs down the centre, and others are visible on either side. Top and sides of the sheet are more or less intact, but it is broken off at the foot and there is nothing to indicate its original height. We may perhaps assume that it would not be much over 30 cm., in which case anything up to fifteen lines of writing are now lost. The writing, which is along the fibres on the recto, is a rather large and loose cursive. The formation of the letters is haphazard, initial letters being not merely enlarged but often eccentrically so (e.g. the δ at the beginning of lines 12 and 18 and the λ of line 16). In addition the scribe was apt to let his pen run dry, making it necessary for him to re-write the last few letters when he had taken a fresh supply, so that in these passages the papyrus has somewhat the appearance of a palimpsest.